Secular Trends of Incidence, Prevalence, and Healthcare Economic Burden in ANCA-Associated Vasculitis: An Analysis of the 2002–2018 South Korea National Health Insurance Database - Ahn, Sung Soo; Lim, Hyunsun; Lee, Chan Hee; Park, Yong-Beom; Park, Jin-Su; Lee, Sang-Won (Frontiers in Medicine, 2022)
Objectives The incidence and prevalence of AAV in Asia remain poorly understood, especially in a nationwide setting. This study investigated the incidence, prevalence, and healthcare burden of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) in South Korea by analyzing a national database. Methods This study included patients with AAV identified from the National Health Insurance Service Database of South Korea from 2002 to 2018. Patients were diagnosed with AAV in a general or tertiary hospital and were registered in the individual payment beneficiaries program or were prescribed glucocorticoids. A calendar-based meteorological definitions were adopted to assess the differences in the incidence of AAV according to season. The average healthcare expenditure and patient outcomes of mortality and end-stage renal disease (ESRD) in patients with AAV were compared to 1:10 age, sex and residential area matched controls. Results A total of 2,113 patients [708, 638, and 767 with microscopic polyangiitis (MPA), granulomatosis with polyangiitis, and eosinophilic granulomatosis with polyangiitis, respectively] were identified. The annual incidence and prevalence of AAV increased continuously, and MPA being the most common disease subtype after 2015. The highest incidence and prevalence of AAV was 0.48/100,000 person-years (PY) and 2.40/100,000 PY in 2017 and 2018, respectively. There were no significant differences in monthly and seasonal incidence of AAV. The average expense of medical care, overall mortality, and ESRD rates of patients with AAV were higher in patients with AAV than in controls, especially in the case of MPA. Conclusion An increasing trend of AAV diagnosis observed is consistent with the evidence that AAV is more common in recent years; however, a relatively lower incidence and prevalence was observed compared to that in Western countries. The higher medical cost and rates of mortality and ESRD in AAV emphasize the early recognition and implementation of optimal treatment for these patients.